1943
DOI: 10.1002/aja.1000720303
|View full text |Cite
|
Sign up to set email alerts
|

The effects of advancing age on the structure of the anterior hypophyses and ovaries of female rats

Abstract: I?VO FIGURESRecent histological observations on the anterior pituitary glands of man (Rasmussen, '36) and of rats (Wolfe, Bryan, and Wright, '38) have indicated that old age is associated with a decrease in the percentages of eosinophiles and an increase in the percentages of chromophobes. The observations on rats were concerned chiefly with a description of the adenomatous changes which occurred in the anterior lobes of the old rats, but the other structural manifestations of advancing age, particularly their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1946
1946
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The microscopic structure of the ovaries of senile rodents has been known for a long time in the rat [Romeis, 1931;Wolfe. 1943;Engle, 1946] and in the mouse [Loeb.…”
supporting
confidence: 40%
“…The microscopic structure of the ovaries of senile rodents has been known for a long time in the rat [Romeis, 1931;Wolfe. 1943;Engle, 1946] and in the mouse [Loeb.…”
supporting
confidence: 40%
“…Similar observations were made by other authors in the adenohypophysis of rabbits (Shionati, 1980), avians (Harrison et al, 1982a,b) and bats (Nunez and Gershon, 1982) suggesting that this process may be related to secretory activity. Wolfe (1943) and Ciocca and González (1978) suggested that the colloid is a bioproduct of cellular degeneration.…”
Section: Discussionmentioning
confidence: 45%
“…Similar changes in pituitary colloid content have been reported previously in numerous mammals. In rats (Wolfe, 1943), cattle (Bassett, 1951) and bat (Anthony and Gustafson, 1984), colloid is a conspicuous component of adult pituitary glands. Colloidal accumulations are rare and reduced in size in immature hamsters, guinea pigs, hedgehogs, and porcine, but these structures are larger and more numerous in older animals (Wolfe and Eaton, 1940;Shanklin, 1948;Hanke and Charipper, 1948;Spagnoli and Charipper, 1955;Curé et al, 1971;Kameda, 1990Kameda, , 1991Ogawa et al, 1996Ogawa et al, , 1997.…”
Section: Discussionmentioning
confidence: 45%
“…This is attested by the fact that ovaries of the aged rat contained vesicular and cystic follicles of varying sizes and numerous corpora lutea. Wolfe (1943), in his extensive study, found a decrease both in follicular and luteal counts in the ovaries of the aged animals.…”
Section: Lhmentioning
confidence: 45%